Effect of low-level laser therapy on bone repair: Histological study in rats - Pretel, Hermes [UNESP]; Lizarelli, Rosane F. Z.; Ramalho, Lizeti T. O. [UNESP] (Wiley-Blackwell, 2007)
Background and Objectives: Bone remodeling is characterized as a cyclic and lengthy process. It is currently accepted that not only this dynamics is triggered by a biological process, but also biochemical, electrical, and mechanical stimuli are key factors for the maintenance of bone tissue. The hypothesis that low-level laser therapy (LLLT) may favor bone repair has been suggested. The purpose of this study was to evaluate the bone repair in defects created in rat lower jaws after stimulation with infrared LLLT directly on the injured tissue.Study Design/Materials and Methods: Bone defects were prepared on the mandibles of 30 Holtzman rats allocated in two groups (n = 15), which were divided in three evaluation period (15, 45, and 60 days), with five animals each. control group-no treatment of the defect; laser group-single laser irradiation with a GaAlAs semiconductor diode laser device (lambda = 780 nm; P = 35 mW t = 40 s; circle minus = 1.0 mm; D = 178 J/cm(2); E = 1.4 J) directly on the defect area. The rats were sacrificed at the preestablished periods and the mandibles were removed and processed for staining with hematoxylin and eosin, Masson's Trichrome and picrosirius techniques.Results: the histological results showed bone formation in both groups. However, the laser group exhibited an advanced tissue response compared to the control group, abbreviating the initial inflammatory reaction and promoting rapid new bone matrix formation at 15 and 45 days (P < 0. 05). on the other hand, there were no significant differences between the groups at 60 days.Conclusion: the use of infrared LLLT directly to the injured tissue showed a biostimulating effect on bone remodeling by stimulating the modulation of the initial inflammatory response and anticipating the resolution to normal conditions at the earlier periods. However, there were no differences between the groups at 60 days.
Keywords: animals; bone remodeling; LLLT